A Review on Recent Rational Approaches to Drug Design, Development and Its Discovery: Pharmaceutical Science-Medicinal Chemistry for Better Drug Design - Dheeraj Bisht; Rajeshwar Kamal Kant Arya; Govind Raj Pal; Ravindra Pratap Singh (International Journal of Life Science and Pharma Research, 2022)
The steps involved in drug design, drug development and drug discovery are highly expensive, extremely challenging and time consuming. Although the drug designing, process has been hastened with the development of newer emerging techniques, and the fabrication of novel computational tool. Researchers are working on structure guided drug designing using a 3-D structure of target, the drug molecule identified by the use of target-based drug design shows great potential in preventing various diseases but also possess many side effects. In the rational drug design, structure-based designing, combinatorial drug designing and computer aided drug design techniques are employed. When gene expression and bioinformatics are incorporated with the combinatorial drug designing, that make the rational drug designing, a more powerful tool for drug discovery. The rational drug designing associated with gene expression and bioinformatical estimation is moderately emerging and expeditiously revamping the drug development with less time consuming, economic, effectiveness and cater novel combinatory therapy in addition to minimization of toxicity. This review discusses in detail about the fabrication of a successful drug candidate using multidisciplinary perspective of combinatorial chemistry with gene expression analysis, structure based and artificial intelligence- based drug designing. In future, more sophisticated computer-based methodologies would be required for developing new drug candidate.